A drop in the bucket of the megadiverse chewing louse genus Myrsidea (Phthiraptera, Amblycera, Menoponidae): ten new species from Amazonian Brazil - Valim, Michel P; Weckstein, Jason D (Folia parasitologica, 2013)
Ten new species of Myrsidea Waterston, 1915 parasitic on members of the avian families Formicariidae, Thraupidae, Tyrannidae, Troglodytidae and Icteridae are described herein. They and their type hosts are M. isacantha sp. n. ex Chamaeza nobilis Gould, M. circumsternata sp. n. ex Formicarius colma Boddaert (Formicariidae); M. cacioppoi sp. n. ex Lanio fulvus (Boddaert), M. brasiliensis sp. n. ex Tangara chilensis (Vigors), M. saviti sp. n. ex Tangara schrankii (Spix) (Thraupidae), M. rodriguesae sp. n. ex Cnipodectes subbrunneus (Sclater), M. cnemotriccola sp. n. ex Cnemotriccus fuscatus (Wied-Neuwied), M. lathrotriccola sp. n. ex Lathrotriccus euleri (Cabanis) (Tyrannidae), M. faccioae sp. n. ex Cyphorhinus arada transfluvialis (Todd) (Troglodytidae), and M. lampropsaricola sp. n. ex Lampropsar tanagrinus (Spix) (Icteridae). Among these are two new Myrsidea species described from the avian family Formicariidae, which previously had only a single described Myrsidea species, and a new host record for M. cinnamomei Dalgleish et Price, 2005 ex Attila citriniventris Sclater. Analysis of mitochondrial cytochrome oxidase I sequences for these and other neotropical Myrsidea species provides an assessment of their phylogenetic relationships and indicates that all of these newly described species are genetically distinct. We also put these descriptions into context by estimating the potential number of unnamed Myrsidea species in Brazil, given the known diversity of potential hosts and typical levels of host specificity for Myrsidea species. Our estimate indicates that Brazilian Myrsidea species diversity is likely more than an order of magnitude greater than the number of described Myrsidea species known from Brazil, highlighting the need for future work on this megadiverse ectoparasite genus.
Keywords: Biodiversity; demografie; Male; Lice Infestations; Brazil; Demography; biodiverzita; mužské pohlaví; Brazílie; nemoci ptáků; ptáci; Birds; zavšivení; Animals; Phthiraptera; ženské pohlaví; zvířata; Bird Diseases; Female